Inferior and anterior QRS fragmentation have different prognostic value in patients who received an implantable defibrillator in primary prevention of sudden cardiac death. (15th September 2017) - Vandenberk, B.; Robyns, T.; Goovaerts, G.; Van Soest, S.; Floré, V.; Garweg, C.; Van Huffel, S.; Ector, J.; Willems, R.
Abstract: Aims: QRS fragmentation (fQRS) has been proposed as a predictor of sudden cardiac death (SCD) and all-cause mortality in ischemic (ICM) and non-ischemic cardiomyopathy patients. However the value of fQRS in patients with a LVEF < 35% is a matter of debate. Methods: All consecutive patients with an indication for an ICD in primary prevention of SCD were included in a retrospective registry from 1996 until 2013. Twelve lead electrocardiograms before implant were analyzed for the presence of fQRS in different regions. Adjusted Cox regression analysis for first appropriate ICD shock (AS) and all-cause mortality was performed. Results: In total 407 patients were included with a mean follow-up of 4.2 ± 3.3 y (age 60.6 ± 11.9 y, 15.7% female and 52.8% ICM). fQRS was present in 46.7% of patients, predominantly inferior (30.7%) followed by anterior (21.4%) and lateral (11.1%) coronary artery territories. fQRS was significantly more prevalent in ICM ( p = 0.004). Inferior fQRS was an independent predictor of a first AS within 1 y (HR 2.55, 95%CI 1.28–5.07) and 3 y (HR 1.90, 95%CI 1.14–3.18) after implantation. Whereas, anterior fQRS was an independent predictor of all-cause mortality within 1 y (HR 4.58, 95%CI 1.29–16.19), 3 y (HR 3.92, 95%CI 1.77–8.65) and the complete follow-up (HR 2.22, 95%CI 1.33–3.69). Lateral fQRS was only a predictor of late (> 3 y of follow-up) all-cause mortality (HR 2.04, 95%CI 1.09–3.81). Conclusions: fQRS in a specific coronary artery territory might be promising to discriminate arrhythmic from mortality risk. Inferior fQRS was a predictor of early arrhythmia, while anterior fQRS was related to mortality.